2016
DOI: 10.1016/j.jchas.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Safety Data Sheets in informing risk based decision making: A review of the aerospace sector

Abstract: Safety Data Sheets are the primary source of hazard information on chemical substances and mixtures and are used to inform risk assessments. It is imperative to ascertain the quality of this primary source of information in informing risk based decision making. The content of Safety Data Sheets (SDS) is governed by regulatory requirements outlined under the Globally Harmonised System for the Classification and Labelling of Chemicals (GHS). However, regulation in itself does not provide assurance of the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Other researchers (Lee et al 2012, Safework Australia 2010, Nayer et al 2015), have examined nanomaterial-related and other MSDSs for quality. 16, 17, 18 They found that the majority of the MSDS did not include sufficient information on the safety of nanomaterials or on how to appropriately inform an occupational risk assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers (Lee et al 2012, Safework Australia 2010, Nayer et al 2015), have examined nanomaterial-related and other MSDSs for quality. 16, 17, 18 They found that the majority of the MSDS did not include sufficient information on the safety of nanomaterials or on how to appropriately inform an occupational risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This left 42% of the SDS as lacking acceptable human health information and 50% lacking acceptable safety information. 18…”
Section: Discussionmentioning
confidence: 99%
“…There are many publications in the chemical literature about SDSs. They range from discussions of what they are, , to who uses them , and how they are used, to how the technical information can be captured and brought onto a readily searchable digital platform. , Kolchinski recently published an article looking at incorrect or erroneous information on SDSs and how such information can lead to safety issues. A further issue raised by most parties impacted by hazard communication requirements is that the intent of GHS was to have a uniform standard for hazard labels and SDSs globally.…”
Section: Introductionmentioning
confidence: 99%
“…European Chemical Agency (ECHA) recommends the use of Safety Data Sheets (SDS) to assure adequate safety information and application of proper precaution of hazardous substances during supply chain, storage, and transportation [6].…”
Section: Introductionmentioning
confidence: 99%